RETAIL TRADE SECTOR IN ROMANIA AND IN THE EU CONTEXT - OANA DOBRE-BARON (Annals of the University of Petrosani: Economics, 2021)
Retail trade is a dynamic sector that has undergone significant changes in recent decades, both globally and within the European Union. As a Member State, Romania must adhere to European trends and at the same time its retail apparatus must respond to the ever-changing needs and preferences of its consumers. This paper aims, on the one hand, an analysis of this sector in Romania over a period of five years to highlight the evolution of the structure of retail enterprises as well as the main indicators that characterize the retail activity, and on the other hand, a comparative analysis, within the EU member states, showing Romania's contribution to the structure and performance of the European retail sector through relevant indicators regarding demographic statistics of enterprises, but also the input and output related variables of an economic activity.